Do food labels affect Turkish consumers’ nutritional choices and expectations? - Yardimci, Hülya; Koç, Nevra (Progress in Nutrition, 2019)
Objective: Food labels are tools that contribute to nutritional education significantly by providing accurate and clear information for societies. The aim of this study was to determine factors having an influence on individuals about reading of food labels, problems they encounter, and nutritional values they want to see on food labels. Subjects and Methods: This cross-sectional study was carried out with 800 individuals aged 20 to 64 years old. A questionnaire form created by the authors was used for data collection Independent Samples t-test and Chi-square (XÇ) significance test were used for statistical analyses. The findings were evaluated at 95% confidence interval and p<.05 taken to indicate significance level. Results: According to results of the study all the participants read food labels. 66.5% of the participants in both genders read food labels because they thought this habit “contributes to healthy eating”, and 55.1% of them thought “information on food labels does not adequately meet their incompetency expectations”. The first two reasons for this incompetency were difficulty in finding production and expiry dates (26.3%) and tiny font size (18.3%). There were significant correlations between some food label symbols (“Gluten free”, “Recyclable”), food label statements (“fiber” and “light”), and gender (p<.05). Expecting to see some food information on labels such as carbohydrates (sugar content), total fat, light, top vitamins, amount of fiber, calcium, sodium, potassium and iron content differed by gender (p<.05). Conclusion: In order to benefit from food labels, rearrangement in all aspects to ensure healthy food choices, and clearer labels may be effective.